Faktor yang mempengaruhi kedisiplinan siswa dan implikasinya dalam layanan konseling di SMA N 3 Sawahlunto - Putra, Rizky Darmansyah; Neviyarni, Neviyarni (Counseling and Humanities Review, 2023)
This study was inspired by a real-world incident that occurred in a school when 5 to 10 children frequently showed up late for class. There are students in and out during class hours and break times. During the flag ceremony, there were still some children who were not fully dressed and noisy. This happened because of the following factors: (1) the similarity of parental punishments; (2) group-approved changes; (3) socio-economic conditions of the family; (4) the concept of the role of parents as adults; (5) student behavior; and (6) unexpected events. The research was conducted at SMA N 3 Sawahlunto. This study uses a quantitative descriptive methodology. 30 people make a research sample. The survey is the instrument used. Factors causing student disobedience Likert scale model. Based on the findings, the high category consists of behavior similar to how parents discipline their children in the medium category, group-acceptable adjustments in the high category, family socio-economic status in the very high category, the concept of the role of adults in the high category, state behavior students in the moderate category, and sudden situations in the high category.